An Empirical Model of Wage Indexation Provisions in Union Contracts - Card, David (Journal of Political Economy, 1986)
Cost of living escalators are an important feature of North American labor contracts. This paper presents a measure of the response of indexlinked wage increases to concurrent price increases for a sample of Canadian contracts, and then analyses this response in terms of a simple model of indexation to the aggregate price level. The model highlights the importance of aggregate price movements in conveying information about industryspecific prices. The empirical analysis confirms that industry-specific correlations between input and output prices and the Consumer Price Index are important determinants of the response of wage to prices across index contracts.